PENERAPAN TEKNIK MODIFIKASI PERILAKU DALAM MENINGKATKAN SEMANGAT BELAJAR ANAK SELAMA “STAY AT HOME” - Aufa Melia Mareta (Alfuad: Jurnal Sosial Keagamaan, 2020)
The spirit of learning in children during COVID-19 is a challenge that is present for teachers and parents. This paper aims to provide a brief description of how behavior modification techniques namely fading, economic tokens, and shaping provide solutions in shaping, maintaining, and enhancing children's enthusiasm for learning during "stay at home". The author uses descriptive methods in analyzing this paper. The results of this paper are that the three techniques (fading, economic tokens, and shaping) are considered effective in shaping the target behavior, that is, children's enthusiasm for learning during the pandemic.